Biogeochemical cycle of mercury and controlling technologies: Publications in critical reviews in environmental science & technology in the period of 2017–2021. Issue 24 (28th September 2022) - Wang, Jianxu; Ma, Lena Qiying; Letcher, Rob; Bradford, Scott Alan; Feng, Xinbin; Rinklebe, Jörg
Abstract: The Minamata Convention on Mercury (Hg) calls for global efforts to reduce the release and risk of Hg. A better understanding of the global Hg budget, transformation and transport as well as toxicity of Hg in the environment, and the Hg emission controlling technologies, is important to minimize Hg pollution and exposure risks. Here, we summarized recent findings regarding the Hg cycle, transport, transformation, and controlling technologies, based on publications in Critical Review in Environmental Science and Technology (CREST) during 2017–2021. In terms of CREST publications we first focused on the biogeochemical cycle and impacts of Hg in the sensitive environment of the Tibet Plateau, and technologies being used to control Hg 0 emission from thermal power plants. Second, we discussed the roles of forest in the global cycle of Hg. Third, we reviewed the transport of Hg at artisanal and small-scale gold mining sites, and the mobility and transformation of Hg species in the environment. This special issue covers the recent studies on the cycle, transport, and transformation of Hg, enhances our abilities to develop better strategies to minimize its risks. There are emerging concerns with climatic change and natural and human perturbations on the biogeochemical cycle of Hg in the environment and futures studies are warranted in these areas as well as the global Hg cycle, transport, and remediation. Graphical abstract: U0001